Establishment of a Breeding Approach Combined with Gamma Ray Irradiation and Tissue Regeneration for Highbush Blueberry - Xuan Yu; Haidi Yuan; Yihong Jin; Chuizheng Xia; Jiani Zhu; Jiali Che; Jiao Yang; Xiaofei Wang; Bingsong Zheng; Shufang Yang; Cristian Silvestri; Fuqiang Cui; et al. (Agronomy)
Blueberries are a relatively recently domesticated species, primarily bred through hybridization. Mutation breeding, which uses chemical or physical treatment to increase plant mutation, has not yet been applied to blueberries. This study introduces a mutation breeding strategy for the highbush blueberry cultivar Vaccinium corymbosum. We established a high-efficiency regeneration protocol, which was applied to leaves and stems exposed to gamma irradiation using 60Co-γ rays at doses of 10, 20, 40, 80, and 120 gray (Gy), to increase the efficiency of mutated cells to develop into adventitious shoots. We determined that the median lethal dose (LD50) was approximately 56 Gy for leaf explants and 80 Gy for stem explants. Phenotypic variations, including changes in leaf color and growth characteristics, which may be due to altered plant response to environmental factors, were successfully observed in the first-generation (M1) plants. The height of M1 plants quantitatively decreased with increasing irradiation doses. To evaluate the mutants induced by each irradiation dose, whole-genome resequencing was conducted on individuals from each dose group, revealing significant genomic alterations at the 80 Gy dose. This approach provides a valuable reference for future blueberry breeding programs aimed at enhancing genetic diversity and improving cultivar performance.